Avaliação do potencial antinociceptivo da Mirabilis jalapa L. em camundongos - Walker, Cristiani Isabel Banderó (2010)
The knowledge about the use of medicinal plants by the population contributed decisively to the modern therapy and the discovery of important mechanisms related to the process of transmission and treatment of pain. A plant widely used in folk medicine is Mirabilis jalapa L. (Nyctaginaceae). The infusion of its leaves is used for the treatment of inflammatory and painful diseases; however, there are no studies confirming its popular use. In this study, we evaluated the potential antinociceptive effects of Mirabilis jalapa in mice. Oral administration (p.o.) of the crude hidroetanolic extracts from leaves and stems inhibited the nociception with ID50 values of 5.5 (2.3 to 13.1) and 18.0 (11.3 to 28.5) mg/kg in a model of acute pain induced by chemical stimulation (test of writhing induced by acetic acid). Among the fractions tested, the ethyl acetate fraction from the leaves (Eta, 10 mg/kg, p.o.) was more effective and potent to induce antinociception with ID50 value of 1.1 (0.6 to 2.1) mg/kg. Thus, this fraction was chosen for further studies. Furthermore, these extracts also inhibited the nociception induced by thermal stimulation (tail-flick test). In addition, Eta (10 mg/kg, p.o.) produced antinociception in models of pain related to arthritis (caused by Freund's Complete Adjuvant (CFA)), neuropathic pain (caused by partial sciatic nerve ligation) and post-surgical pain (induced by incision in the paw of mice). Only the repetead administrations of Eta (10 mg/kg, p.o.) cause a decrease in paw edema produced by CFA. The antinociceptive effect of Eta (10 mg/kg, p.o.) was not reversed by pretreatment with naloxone (2 mg/kg, i.p.), but by atropine (5 mg/kg, s.c.) or mecamylamine (0.001 mg/kg, s.c.). As the participation of the cholinergic system in antinociception was induced by this fraction, we determined the effect of Eta on the activity of acetylcholinesterase (AChE) in vitro and ex vivo. The in vitro activity of AChE in blood and spinal cord of animals was not altered by Eta (1 and 10 mg/mL). In the ex vivo assay, an increase of enzyme activity in the spinal cord of mice treated with CFA, which was completely reversed with the administration of Eta (10 mg/kg, p.o.), was observed. With regard to adverse effects, Eta (10 mg/kg, p.o.) did not alter locomotor activity, body temperature or gastrointestinal transit, nor produced gastric lesions. These results demonstrated that M. jalapa shows antinociceptive activity in mice, confirming its popular use as an analgesic.